Interview: The challenges of financing basic education in the context of the new Fundeb - Profa. Dra. Nalú Farenzena - França, Magna (2021)
This interview addresses the issue of financing basic education in Brazil. The interviewee's relevant experience in this field of knowledge provides insights that make it possible to understand the theme with regard to the relationship between finance, quality and evaluation; the new tax regime established by EC 95/2016; the reduction in education investment during the Covid-19 Pandemic; fund policies; to the innovations that the so-called permanent Fundeb offers. It also highlights the main guidelines for academic associations and civil society entities, especially Fineduca, in the battle for the financing of education that guarantees, in fact, the right to education.